If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + (-6n + 4) = -1(-9n + -5) + -5 Reorder the terms: -8 + (4 + -6n) = -1(-9n + -5) + -5 Remove parenthesis around (4 + -6n) -8 + 4 + -6n = -1(-9n + -5) + -5 Combine like terms: -8 + 4 = -4 -4 + -6n = -1(-9n + -5) + -5 Reorder the terms: -4 + -6n = -1(-5 + -9n) + -5 -4 + -6n = (-5 * -1 + -9n * -1) + -5 -4 + -6n = (5 + 9n) + -5 Reorder the terms: -4 + -6n = 5 + -5 + 9n Combine like terms: 5 + -5 = 0 -4 + -6n = 0 + 9n -4 + -6n = 9n Solving -4 + -6n = 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -4 + -6n + -9n = 9n + -9n Combine like terms: -6n + -9n = -15n -4 + -15n = 9n + -9n Combine like terms: 9n + -9n = 0 -4 + -15n = 0 Add '4' to each side of the equation. -4 + 4 + -15n = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -15n = 0 + 4 -15n = 0 + 4 Combine like terms: 0 + 4 = 4 -15n = 4 Divide each side by '-15'. n = -0.2666666667 Simplifying n = -0.2666666667
| 1/2(4)+3 | | z-30=19 | | 72X+7Y=320 | | -8+(-6n+4)=-(-9-5)-5 | | -3/4x=7/2 | | a+29=30 | | -11k+16k=85 | | z-27=19 | | X^2-7xy-8y^2=0 | | 16x^2+32+15=0 | | 12(x-7)+4(2x+2)=50x-62 | | 6d+4=2d+28 | | 2x+9=34 | | 4-3(-6(2+3)+4)= | | -6x^4+59x^3-292x^2+429x-290=0 | | 8x^3-8x= | | 4x+3+5(2x-1)= | | 9+6(-4n-2)=-2(-5+2)-8 | | 2x=(3/2-x) | | 7e-7=60.2 | | 14+4x=-7+12x | | 14+4x=12x-7 | | 4x+14=12x-7 | | 9x-4=11x-10 | | 5(a+3)=45 | | 27=-3(6) | | (1/3)(y+17)=3y-5(y-3) | | 9=7c-5 | | 12x-7=4x+14 | | 5.3x+1=3.8x-11 | | 2(3x-6.5)=20 | | (3x-8)+(2x+5)-(4x-8)= |